2017
DOI: 10.1093/med-psych/9780190685973.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Unified Protocol for Transdiagnostic Treatment of Emotional Disorders

Abstract: The Unified Protocol (UP) for Transdiagnostic Treatment of Emotional Disorders: Therapist Guide is a treatment programv applicable to all anxiety and unipolar depressive disorders and potentially other disorders with strong emotional components (e.g., eating disorders, borderline personality disorder). The UP for the Transdiagnostic Treatment of Emotional Disorders addresses neuroticism by targeting the aversive, avoidant reactions to emotions that, while providing relief in the short term, increase the likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
125
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 0 publications
0
125
0
6
Order By: Relevance
“…In this part of the treatment, the therapist helps the authorities identify emotional patterns and emotional-driven behaviors. After the cognitive authority has more to do with the effects of these behaviors on continuing discomfort, measures are taken to change the current patterns of emotional responses (3). The most recent psychopathological theories emphasize the role of emotions in developing, maintaining and continuing the symptoms of emotional disorders and many other mental disorders (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this part of the treatment, the therapist helps the authorities identify emotional patterns and emotional-driven behaviors. After the cognitive authority has more to do with the effects of these behaviors on continuing discomfort, measures are taken to change the current patterns of emotional responses (3). The most recent psychopathological theories emphasize the role of emotions in developing, maintaining and continuing the symptoms of emotional disorders and many other mental disorders (24).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that marital conflicts and communication problems can play a key role in the incidence and exacerbation of depression symptoms (1,2). Depression is an emotional disorder, and emotional regulation is an important mechanism contributing to the formation of emotional disturbances (3). Emotional regulation also affects interpersonal relationships, especially marital relationships (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomena mentioned above are strengthened by the statement of Barlow et al, (2017) that individuals who are unable to control emotions are easily frustrated, anxious and resolve problems in emotional ways. Adolescence have not been able to control emotions more precisely and express emotions in ways that are accepted by society (Santrock, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It may also be more effective when these processes represent the most central maintaining variables for some or all the presenting comorbid conditions. Though several transdiagnostic interventions are available (e.g., Barlow et al, 2017;Hayes et al, 2012;Norton & Philipp, 2008) we present the Radically Open Dialectical Behavior Therapy (RO DBT; Lynch, 2018) approach in this manuscript because it is not yet well-known, it involves new theoretical perspectives and treatment procedures, and because it concentrates on mechanisms of change not previously emphasized.…”
mentioning
confidence: 99%